Microestructura de las escamas dorsales de nueve especies de serpientes costarricenses (Viperidae) - Arroyo G., Olga; Cerdas, Luis (Revista de Biología Tropical, 1986)
Since taxonomy within this family is sometimes controversiaI, the morphology of scales might become a useful tool in the study. In this work we analyzed the microomaments of the scales of 9 Costa Rican species from the family Viperidae with a Scanning Electron Microscope. Scanning electron microscopy revealed that the microornaments of dorsal scales of nine Costa Rican Viperidae are characteristic of each species. Moreover, the scale pattern in individuals from the same species is identical, independently of their anatomic location. There are no differences between scales of specimens of B. asper collected in the Atlantic and Pacific regions of Costa Rica.